PEMANFAATAN APLIKASI SPSS UNTUK MENINGKATKAN KETERAMPILAN SISWA DALAM MENGOLAH DATA STATISTIKA - Aruan, Anggie Desi K.; Manalu, Ayu Nasari; Manik, Efron; Hutauruk, Agusmanto J.B (JURNAL CURERE, 2023)
The development of Technology and Information is running so rapidly. The technology is not only intended to facilitate human work but also intended to facilitate humans in teaching and learning.  One technology that is widely used to help facilitate human work, especially in the field of statistics, is the SPSS (statistical program for social science) application.  The use of this application in learning statistics courses is absolutely necessary to help make it easier for students to process data at the time of completing the final project. This study is an experimental study with a population of all students who contract statistics courses. Based on the results of the data analysis conducted, the numbers 2,98 > 1,97 were obtained (the t-count value is greater than the t-table value).  Based on the results of the analysis, the hypothesis (Ha) is accepted and the hypothesis (Ho) is rejected.  Because the t-count value is greater than the t-table, the results of this study can be concluded that there is an influence on utilizing the SPSS application on improving students' skills in processing statistical data.